Chitosan-based biomaterials used in critical-size bone defects: radiographic study in rat's calvaria - Spin-Neto,Rubens (2012)
OBJECTIVE: This study evaluated, using digital radiographic images, the action of chitosan and chitosan hydrochloride biomaterials, with both low and high molecular weight, used in the correction of critical-size bone defects (CSBD's) in rat's calvaria. MATERIAL AND METHOD: CSBD's with 8 mm in diameter were surgically created in the calvaria of 50 Holtzman rats and these were filled with a blood clot (Control), low molecular weight chitosan, high molecular weight chitosan, low molecular weight chitosan hydrochloride and high molecular weight chitosan hydrochloride, for a total of 10 animals, which were divided into two experimental periods (15 and 60 days), for each biomaterial. The radiographic evaluation was made using two digital radiographs of the animal's skull: one taken right after the bone defect was created and the other at the moment of the sacrifice, providing the initial and the final radiographic bone density in the area of the defect, which were compared. RESULT: Analysis of radiographic bone density indicated that the increase in the radiographic bone density of the CSBD's treated with the proposed biomaterials, in either molecular weight, in both observed periods, where similar to those found in control group. CONCLUSION: Tested chitosan-based biomaterials were not able to enhance the radiographic density in the CSBD's made in rat's calvaria.